El fin de la opresión de los pueblos: la supresión de los subdelegados como restauración de las libertades de los pueblos chilenos en la crisis de la Monarquía española (1810-1811) - Enriquez, Lucrecia (Anuario de Historia de América Latina, 2025)
In 1811 the Governing Board of the Kingdom of Chile suppressed the subdelegates but not the subdelegations, created by the regime of intendancies established in Chile in 1786. They justified the measure because it was the oppression of the towns. The powers of the subdelegates were exercised by the ordinary mayors of the towns councils. This article analyzes this modification of the intendancies regime as a restoration of municipal liberties and from the perspective of the collective resistance of the councils in the crisis of the Spanish Monarchy.